ENGINEERING GEOLOGY PROBLEMS OF THE COASTAL ZONE AROUND ANCIENT ABDERA, XANTHI, N. GREECE. - Δελημάνη, Π.; Ξειδάκης, Γ. (Bulletin of the Geological Society of Greece, 2018)
The main engineering geology problems of the coastal zone around Ancient Abdera together with their causes are examined in this paper. The area studied extends from the coastal settlement of Mirodatc» up to the coastal settlement of Mandra, Xanhti prefecture, N. Greece. A geomorphology classification of coasts of the area is presented and maps of the ground inclination and geotechnical zone are constructed. The main geotechnical problems of the area appear to be: inundation of much of the area during winter period; foundation settlement; shallow water table; pollution of the groundwater and arbitrary construction in environmentally protected zones. The area of study gets special interest due to its continues human habitation since the 8 th B.C. century. As it has come but from archaeological and sentimentology studies, the Abdera bay has suffered (long shore bar) and land (torrents, load) results in quick filling in the ancient harbors, making them in navigable and forcing the habitants to more their harborworks further south to deeper sea water.